GAYA BAHASA BERDASARKAN STRUKTUR KALIMAT DALAM PANTUN ADAT JAMBI - pri yanto (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2016)
The purpose of this research is to describe the style of language based on the structure of the sentence contained in the traditional pantun Jambi. The method used in this research is a qualitative descriptive method, with a stylistic approach. The data in this study is the style of language based on sentence structure. The data source in the research is the rhyme contained in the book